(untitled) (Eureka Journal of Business, Economics & Innovation Studies, 2026)
Successful entrepreneurship requires addressing a wide range of challenges, including the choice of logistics services within the company, specifically the method for managing material and associated flows from raw material sources to the end consumer. The choice may be made in favor of one of two options: independently managing logistics flows or involving additional participants, including logistics providers, in the supply chain management process.